Bogency and Goodacies: On Argument Quality in Virtue Argumentation Theory - Fabio Paglieri (Informal Logic, 2015)
Virtue argumentation theory (VAT) has been charged of being incomplete, given its alleged inability to account for argument cogency in virtue-theoretical terms. Instead of defending VAT against that challenge, I suggest it is misplaced, since it is based on a premise VAT does not endorse, and raises an issue that most versions of VAT need not consider problematic. This in turn allows distinguishing several varieties of VAT, and clarifying what really matters for them.